2002
DOI: 10.1046/j.1365-2648.2002.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the skills for family planning nurse prescribing: development of a psychometrically sound training needs analysis instrument

Abstract: The results indicate that the modified instrument is valid and reliable and therefore can be used with confidence to assess the training needs of FPNPs. In addition, the factors have outlined a cogent definition of the role of the FPNP, which can be used both to inform educational programmes and to assess their efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…1999, Stewart 1999, Riley & Peters 2000, Sapountzi‐Krepia et al. 2001, Hicks & Tyler 2002) the type of factor analysis used was not specified and other information was also omitted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1999, Stewart 1999, Riley & Peters 2000, Sapountzi‐Krepia et al. 2001, Hicks & Tyler 2002) the type of factor analysis used was not specified and other information was also omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it serves to illustrate the use of factor analysis in JAN. In the earliest paper, retrieved in this review, in which the use of factor analysis was reported (Lundman 1988) the type of factor analysis used was not specified (nor the method of selecting the number of factors to be extracted) but in papers published at the turn of the Century and as recently as 2002 (Bond et al 1999, Stewart 1999, Riley & Peters 2000, Sapountzi-Krepia et al 2001, Hicks & Tyler 2002 the type of factor analysis used was not specified and other information was also omitted. It was not possible to calculate a subject to item ratio in five papers and this omission spanned from 1989 (Whetstone & Hansson 1989) to 1999 (Bond et al 1999) and the reasons varied: in some cases no information at all was provided about either the sample size or the number of items.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hennessy-Hicks Questionnaire is depended on self-assessment, it was validated, adapted by World Health Organization (WHO) and used before in different health professions, like nurses, midwives and primary healthcare team (7)(8)(9)(10)(11). Self-assessment for professional medical laboratory technician (12) and the emergency medical technician was also studied (13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, training needs analysis instruments make the questionable assumption that individuals completing the analysis have an insight into their own training needs and can prioritize those needs (Hicks & Hennessy 1998). Despite the production of dubious tools, recent evidence indicates that there is a growing interest in the development of training needs analysis tools that aim to meet the strict criteria of validity and reliability (Sheperd 1994, Maloney & Kane 1995, Jeffreys & Smodlaka 1996, Thomson & Kohli 1997, Farrell 1998, Hicks & Hennessy 2001, Hicks & Tyler 2002). Sadly, some of these studies lacked rigour in that it was not clear what themes informed the survey questions or where this data originated (Thomson & Kohli 1997); whether any form of validity or reliability analysis had been performed (Thomson & Kohli 1997, Farrell 1998); or the training needs analysis tool only assessed a specific aspect of training needs disregarding the statutory and organizational needs (Maloney & Kane 1995).…”
mentioning
confidence: 99%
“…Conversely, Hicks and Hennessy (1996) incorporated the personal, organizational and statutory aspects of a training needs analysis instrument into their tool, by grouping tasks into five super‐ordinate classifications namely: research/audit activities; communication/teamwork; clinical tasks; administration/business activities and management supervisory tasks. Using these categories, the Hicks and Hennessy tool has been used and adapted repeatedly, and on all occasions the tool has been shown to be valid and reliable (Hicks & Hennessy 1997a,b, 1998, 1999, 2001, Hicks & Tyler 2002).…”
mentioning
confidence: 99%